Acetylated microtubules are required for fusion of autophagosomes with lysosomes - Xie, Rui (BioMed Central, 2010)
BACKGROUND: Autophagy is a dynamic process during which isolation membranes package substrates to form autophagosomes that are fused with lysosomes to form autolysosomes for degradation. Although it is agreed that the LC3II-associated mature autophagosomes move along microtubular tracks, it is still in dispute if the conversion of LC3I to LC3II before autophagosomes are fully mature and subsequent fusion of mature autophagosomes with lysosomes require microtubules. RESULTS: We use biochemical markers of autophagy and a collection of microtubule interfering reagents to test the question. Results show that interruption of microtubules with either microtubule stabilizing paclitaxel or destabilizing nocodazole similarly impairs the conversion of LC3I to LC3II, but does not block the degradation of LC3II-associated autophagosomes. Acetylation of microtubules renders them resistant to nocodazole treatment. Treatment with vinblastine that causes depolymerization of both non-acetylated and acetylated microtubules results in impairment of both LC3I-LC3II conversion and LC3II-associated autophagosome fusion with lysosomes. CONCLUSIONS: Acetylated microtubules are required for fusion of autophagosomes with lysosomes to form autolysosomes.